The Enhancement Of Students’ Speaking Skills Through Heuristic Strategy - Maulana, Fadla Yazidah (Published by Institut Teknologi Pendidikan Indonesia, 2024)
This study aims to find out whether or not the Heuristic strategy able to enhance students' speaking skills. There were a number of 27 students in grade 8 participating in this quantitative study with experimental research design. These students were registered at SMP Global Insani School, Bogor and were selected through cluster random sampling. In collecting the data, the researchers used validated pre- and post-tests of speaking as the instruments. The data were analyzed statistically through paired sample test to find out the results of the research. The analysis revealed that there was significant difference achieved by the students in terms of speaking achievement both in the pre-test and post-test. This result was proven by the result of significance value (2-tailed) p = 0.000, <0.005, hence, the null hypothesis ((H0) was rejected and the alternative hypothesis (Ha) was accepted. Thus, this research study concluded that Heuristic strategy enhanced speaking skills of grade 8 students of SMP Global Insani School, Bogor.